Allocation of Village Funds and Socio-Economic Autonomy Of Village Communities: A Case in Senduro Village, Lumajang Regency - Umar Sholahudin; Abdus Sair (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2022)
This article will review the implementation of ADD and its impact on the Socio-Economic autonomy of the Senduro Village Community. So far, research on villages is still about the condition of villages and village communities and their problems. Meanwhile, those relating to the implementation of ADD and its impacts have not received much attention. In fact, the village fund allocation policy (ADD) is believed to be able to contribute to the improvement and improvement of village autonomy, especially in the socio-economic field of rural communities. This article is the result of research using qualitative methods and descriptive approaches. The results of this study indicate that the implementation of the ADD policy in Senduro Village is carried out according to the needs of the village community. Two needs were identified, namely the establishment of Senduro as a Traditional Village and the Development of a Tourism Village. The implementation of these two village needs has an impact on the socio-economic independence of the village. Programs and activities for the establishment of Traditional Villages and the Development of Tourism Villages are carried out in a spirit of togetherness and mutual cooperation. Strong social ties among citizens are able to build community economic independence. The implementation of ADD in mutual cooperation is able to build the socio-economic independence of the people of Senduro Village to be more productive.